Oral history interview with Anastasios Michos / Interviewee Michos, Anastasios Date interview: 2014 November 15 Language Greek Extent 1 digital file : MPEG-4. Credit Line United States Holocaust Memorial Museum Collection, courtesy of the Jeff and Toby Herr Foundation (United States Holocaust Memorial Museum, 2014)
Interviewee Michos, Anastasios Date interview: 2014 November 15 Language Greek Extent 1 digital file : MPEG-4. Credit Line United States Holocaust Memorial Museum Collection, courtesy of the Jeff and Toby Herr Foundation: BEEP Good morning, thank you very much for coming to see us. Can you tell me your name? My name is Michos Anastasios. When were you born, Mr Michos? I was born in 1929 in Kourisos, Kastoria. What is Kourisos? Kourisos is a village 15 km east of Kastoria. And in your family, what position do you take? How many brothers did you have? We were seven brothers, six boys and one girl. I was the youngest. When I grew up, of course, I finished high school in the village and then I went to high school in Kastoria. Why Kastoria? Who was there? In Kastoria, my brothers and my father had a coffee shop. The coffee shop was in the center, facing west, and the other door behind the coffee shop was facing the market, the commercial area. So we went to high school and I lived more until 1947. I was more in the coffee shop, less at home, because I was helping, but I was eating there. And I was helping more in the coffee shop, to offer water, to offer coffee and so on. Who were the customers of the coffee shop? The customers of the coffee shop were originally from Kastoria. And because the coffee shop was in the center, many people came from the villages, especially on Monday, when the market was open. We had Jewish customers who went to the coffee shop, but not as customers playing cards or playing cards. I never saw a Jew playing cards or cards. Did the coffee shop have Jewish shops nearby? Quite a few, quite a few. Can you describe them to us? Did you go to the cafes? I went to the cafes, yes. So you know them. Who were they? I remember the representative of the singer machines, from the machines, it was Eliaou. Also the opponent, Kocso, that's what we called him, I don't know if it was the opponent or his name, who had many children, he sold oil. I'm talking about the back side of the coffee shop, which was two-door. And his son, the musician, an unforgettable musician, sold oil. These two were the most important ones that I remember well. The other Jews were in the upper market. In other words, in which areas did the Jews live? The Jews, the synagogue was behind Tzarsi, as we say, on the back side. You could see towards the south. It was around there, but also from the gymnasium, as the gymnasium was on a hill, to go up from the main road, it had about 50 steps. Just opposite, there were many Jewish houses and shops. Among them was a classmate of mine who lived in the same synagogue. What was his name? Alberto Cohen. So you had Jewish classmates? In the same synagogue. And a minister. Also, another Cohen, who was short and sat in front of me, in Thrania, was the son of a Cohen who had the big fabric store opposite the palace. What was the palace? The palace was the hotel. I don't know if it still exists today. Below, there were theaters, cinemas, events that took place, and above was the hotel. Just opposite was the big store of Cohen. Did the Jews listen to other professions other than commerce? I can say that I don't remember a single Jew selling shoes. Every house in Kastoria had a room, a workshop, with shoes. I don't know if there were any Jews. But with commerce, they were the first. So there were no poor Jews in Kastoria? There were poor Jews, but the ones I knew were the Hamalids, the Bastasids. They were the poor ones. The rest were well-off. Do you remember any other characteristic Jews of Kastoria? First of all, Telali. He was tall, with a moustache, like this. I remember him in every democracy that took place in our coffee shop. He would say something like, He would say something like, He would say something like, I knew a lot of other Jews, but I don't know how to describe them. Do you remember them? Yes. The poor Jews, apart from the Bastasids, the rest were well-off. Why did you tell me earlier that Mosikos was the unforgettable one? There's a long story. A gifted boy had the other door on the back of our coffee shop, right across the street, and he would constantly ring the bells. When the Jews gathered and disappeared from Kastoria, after the liberation, Mosikos came to us. Mosikos was a fat boy, and he probably lived off of himself, eating his sausages. When he came to Kastoria, he was like a lamp. When he came to the coffee shop, he described his liberation from the army, and how he saw Zhukov, the Soviet soldier, who made a parade and showed us how he saw Zhukov in the coffee shop. As soon as he arrived, on the first day, they took Mosikos and sent him to the church. Outside the church, there was a kind of sanatorium, so that he could receive his health. In a few days, however, he came back. Again, with the same profession. Then, I learned that he went to the Volos. I never saw him again. Did he tell you which army he had gone to? No, I don't remember. He just described his liberation to us. What was the attitude of the Jews in the market? Their commercial attitude? They were people who made an agreement. They made a bargain. The Jew wouldn't let you go without buying something. Even if it was cheap, he wouldn't let the customer go. Didn't the customers make a bargain with the Christians? They did, but not like the Jews. Do you remember any discussions between Jews and Christians in the market? Of course, the characteristic that I remember, and I was impressed afterwards, was that there were two Jews and one Christian, and they were both shepherds. The Christian said, they will give you a massage. Back then, we still had Italians, not Germans. How did he know? I didn't know. He said, they will take the women to Italy. Because we were the only ones there. That was one characteristic. The discussions were not something that impressed me. Is there any other story about the relationship between Jews and Christians, or villagers, or in the city of Kastorgasi, in the surrounding area? Until the Italians came, the Jews were free. They came to the villages outside. I remember that in my village, there was a big field, and inside there were fields. There were fields and a well. When the women came to buy, they would take out the field, and with the well, they would count the harvest that each woman wanted. There is a characteristic that I remember, after I realized it, that my niece, who was a big girl, told me. She had gone to their house. Which house? The house in Gorisso, in Gorisso. The Jew, with his stuff. And the Jew said, I don't know if I will be able to come back here. And he said, why? And he said, let's hide you from us, the grandfathers. We will make a fool of you, I don't think it will be appropriate, we will expose you. And indeed, he didn't come back. The policy changed, the Germans came, and the evil began. Before that, you had started to tell me, and I understood, that the Jews were free in the Italian occupation. What I am telling you now, was a Jew in my village, who came with his stuff. They allowed it, they couldn't take them out. Then, when the Germans came, they put the star on them. Forgive me a little, tell me a little more about the Italian occupation. Were the Italians so good? It wasn't the Germans' way. But, they didn't do us any harm, except, they made us slaves to the animals, to the villages, who wanted to have meat, to get for the army, and it was proven later, that the Italian governor, made it a trade. And he was sentenced to death, he was executed. His name, Leli, doesn't go away now, the Italian name. Otherwise, we didn't have a serious problem with the Italians. So, there was no violence in the Italian occupation? No. Only in relations? Yes, I went to the villages, and made settlements, to feed the army. We didn't have anything else. What changed with the arrival of the Germans? The Germans left. I don't know if they surrendered, or they fled to Albania. I don't know. The characteristic was that, they marked the Jews. They all put a star on their cap. Did you see it? Of course, they were coming out. And, from then on, of course, the harshness of the Germans, in the whole area, was known. We had, in Glisoura, by the way, two Germans were killed, and a group of Germans came, and killed 130 women. They went into Glisoura, and killed those who were alive. That was a counter-murder. A counter-murder, because they killed the Jews. Something similar, that is combined with the Jews, is about my village. Outside the village, before we arrived, from Kastoria to Koriso, two Germans were killed again. As soon as people found out, they went to the surrounding areas, to hide as a counter-murder. That was when they gathered the Jews, for their transfer. I was in Kastoria. Those Germans were killed, and my compatriots were afraid, and they went outside to hide. At that time, however, the Germans were busy with the gathering of the Jews. On the other hand, this is characteristic, a man named Tsiphoras, who had good relations with the Germans, took an officer with him, and went to the village. This is what the whole village says. I was in Kastoria. The whole world says this. On a Sunday, he brought him to the church. The service was over. He told him that these people, while the people were leaving the church, were religious people, quiet, and had nothing to do with the counter-murder that the Germans did. On the one hand, this is the fact. The Germans were busy with the gathering of the Jews, so they left the village. The church was not affected. In your narrative, you say that you were in Kastoria, and that the Germans in Kastoria were busy with the gathering of the Jews. Of the Jews. So, did you see anything from this gathering? I have a long history. When they started gathering the Jews, I don't know, because he was my classmate, or because I had a good relationship with him, with Alberto, I went to his house. Alberto's house was on the lower side of the school, and I went to see him, and there I saw his whole family, his mother, his father, with the boys, and they were waiting. At one point, the German came, and took them out to accompany them. Excuse me, I would like to ask you, how did the German know that the Jews lived in this house? The houses of the Jews were all marked. I don't remember if they were marked from then on, but later I saw that in the shops, and in the houses, they had put a sign on the doors. I don't know what it said, but this house is Jewish, or I don't know what the paper said. When did they put the sign? I saw this house after the Jews left. Before you told me that the houses were marked. Yes, because I knew them. What were they marked with? No, that's what I meant, with the sign they put on the doors. Now, the Germans knew where the Jews were, one house was marked. They knew where to go to Alberto's house. Do you know who had marked them? The Germans had marked them. By themselves? Yes, by themselves. When we say, there will always be someone. Did you know anyone like this? No. Like this Tsifora? No, Tsifora didn't do such a thing. He was an independent man, and I knew about the Italians, especially from the villagers, Koutourikos. He was from Blachos, but he knew about Blachika, and it seems that he had a good relationship with the Italians, and he was an interpreter. But he was for the Italians, not with the Germans. I didn't know anyone like this, with the Germans, or as an interpreter. Now, the fact that they knew the houses of the Jews, I don't know how I recorded them. So, when I went to Alberto's house, the Germans put them outside, with the Germans, and I went with them. They had the star, of course, and I took one bag from Alberto, one bag, and we went from the gymnasium, and from Katiforos, to the gymnasium of Sileon. That's where we went. We went together, and I remember a characteristic, that in front of us, there was Mazalto, a well-known girl, who was shouting, where are they taking me? My little house. I remember her words vividly. And all together, the German had five or six people with him, another German had another group from other houses, and they went to the gymnasium of Sileon, which is under the Dixamini, from the highest point of Kastoria, to the northern part of the lake. We went there, I went to the yard, together with Alberto, I left him there, and I left. The others went. I didn't go inside, I don't know. There were only a few steps, three or four steps, and you entered the gymnasium. In the yard? Were there people? Were there Kastorians? No, no. They put them inside. Other Kastorians, like me, where I went, others might have gone too, but I don't remember them like that, there were only a few people. What did you hear from outside? What? Where are they going? What are they doing? There, of course, I remember, it was opposite the palace, there were two houses of Jews, of the Neoclassical type, stone-built, who had, they were the owners of a mill, of a mill, in Dombiltsa. Dombiltsa was down the street, it produced a lot of water, and a group came from above. Up there was the mill, which must have been a water mill, I didn't see it. But I knew that the mill was there, the people who have the two houses, the nice houses, which were two little girls, and the people, when the Jews took them, they were talking about the girls who took them with them. Do you remember names? No names, I don't remember them, I don't know them, I don't remember giving them to them, but they are known, because they were rich, good businessmen, and they were the mills, the mills that worked, probably, the mills, I didn't go up there, because it was more than 200 meters higher than the road down Dombiltsa. Today it is the supermarket of the union of maintenance, that location, where the water was. A little further up was the mill. But I saw every day, from the coffee shop in front, a cart with horses, loaded with flour, and they were going up to distribute the flour to the mills. And in fact, in our coffee shop in front, the load starts to go to the cart, and the same mills put their strength to get the horses out of the load. These things, they passed every day, the carts with the flour, to distribute the flour to the mills. These flour came from the mills of two Jews, whose house, the houses, they were two separate houses, became the German guardhouse. There was the German guard afterwards, where the Jews left, not when the Jews left, but when, before the Jews left, the German guardhouse and these two houses. Have these houses been saved? I don't think so, because, probably not. It is so characteristic, that whoever asks in Kastoria, should know. Opposite, next to the palace, which is above the hotel, below a large room, absolutely next to it, was the Stathis' oven. But I was also a student of Stathis. Exactly opposite, are these two houses. But today, I don't think they have been saved. There must have been many houses. The gymnasium where they went, has it been saved? Does it have a name? Has the building been saved? A few months ago, I was in Kastoria, and I went up, for an event that happened with my family, to a memorial, and I was sitting on the porch with the children, and I was telling them, exactly opposite, the house where I was sitting, next to Kallithea, just opposite the gymnasium. Of course, Kallithea, you go down to the market, and you go up to the gymnasium, at a great distance. And I was telling them, that that's where the Jews met, and they told me, that there is a memorial there. I didn't go there yet, and I didn't notice it. But they told me, that there is a memorial, and next to that memorial, there is a building, that must have been the gymnasium of Stelion, in the same building. I think so. And it's a shopping mall, I don't remember how the children call it. Mr. Taizo, how many days did the Jews keep them there? They shouldn't have kept them for long, because when Roberto informed me, on the second day, or the third day, I was sitting in the coffee shop, and there was a man, named Tarampanis, from Madrochori. He was my classmate, but he was older than me, because back then, many of my friends were older than me. And he told me, that Roberto gave us some bread, but I didn't ask him, how did he end up there? Maybe for some reason, with someone he knew, I don't know. I said, are they leaving? The Germans? They are leaving, I was there. So, I cut the village, as they brought us a lot of bread, we had half a bread, which means an oka, one and a half kilo. I cut a quarter of it, I put it on a piece of paper, and I went. I went, there was a German, outside, naked, on the steps, two or three steps, that the gymnasium had, there was a Jew. Did you know him? No, I knew him as a Jew, but I don't know, I don't even remember his name. And, when I went there, and I told him about Alberto, he yelled at him, and Alberto went down. Alberto went down, as we started from his house, to the gymnasium, where we didn't take our shoes off, and at that moment, I gave him the bread, and we didn't say anything. So, quietly, we broke up again. I never saw Alberto again. Did you see, finding Alberto, other Jews, that you knew there? How? The Jews were, in our cafe, where they passed, or went to the shops, very famous. But, in there, I don't know, how they were, they were all, all the Jews, that were in the gymnasium, gathered there. But, I don't remember, but, now, names, for God's sake, Eliyahu, Kocho, Cohen, who had the big shop, on the, on the, on Sarsidia, opposite, a little further, from the palace. I saw many names, that I can't, I can't remember now, but... How did you get so close, there, at the door, from the building, that was crowded? Did you hear anything, that the Jews were saying? No, I didn't go inside, that, inside, the building. What was going on outside? Nothing, silence, they were all inside, closed. And, only one Jew, was at the, at the door, they were sitting well, apparently, for communication, for, to him, to him, I said, and he shouted, and Albert came down. Albert came down, and the people, that people today have, and they are hugging, and they are kissing, and they are saying goodbye, they weren't worried as much, he gave him the bread, a little piece of bread, and left. And then what did you do, Mr. Tarsos, you left from there, you went to... I went down to the coffee shop, I went down. How, how much, how much time passed. Now, there, these days, if it was the second, or third day, then they took them. Now, how many days were there and and they took them. I can't tell you exactly, but it was two to three days. Did you see their migration? Of course. When I say that I saw a truck in front of me, the Jews were going up, but not all of them. The others had to take them from the high school to the university. They couldn't go by car. The ground was steep, but in a high school, where the road is horizontal, they had to be loaded from there. I didn't examine that. And you saw how they were loaded. Yes. And how did you see that? A truck with a tent on top of it. They lifted them up and closed the tent. Who were those who lifted them up? The Germans. The Germans. I mean, did the Jews have the children with them? I can't remember if they were small children, but they had gathered all the Jews. How long did you sit and watch? I can't confirm that now, but I saw the truck being loaded without the others seeing it. I didn't see Alberto getting into that truck. They had to load him on top of the truck. And what was the situation of the Jews who were being lifted up? They were as sad as they were, and they continued to have the star on their chest. Was there anyone else from Kastorianos nearby who was watching how they were being lifted up? Yes, of course. We were sitting in front of the door. The runway was big. We had tables. There were others. I don't know. I don't remember who it could have been. Did the Kastorians say anything to each other? Well, what I remember about the crime was the girls who had their apples and their houses. They were two beautiful girls. I remember how the Kastorians were pampering the poor girls. What else? Did you see the trucks leaving? No. Only one truck. I don't know about the others. At what speed? They were taken to Aminio. Because that's where the train was going. And where was that train going? It was going to Thessaloniki. And the musician, when we asked him what his father was doing, he said, they don't exist. And as Mr. Stern told us, his father, because he was a bit fat, died in the train. From Thessaloniki to Eksa. Before he arrived? No, before he arrived. Where they had gathered them in Dachau, I don't know where they had gathered them. Do you know if that was the last truck that took Jews? Or was there more? What? The one you were watching. No, there was more. The others didn't pass in front of them yet. So it was on the Eitanasi. You didn't see that? I didn't see it. I was wondering what happened to the others. And how many hours did it take for all the Jews to leave? I can't tell you specifically, because I didn't see them leave. You only saw that? That's all I saw. The other day, when it dawned, were there any Jews in Kastoria? No. No one was hiding? No one was hiding. I don't remember anyone hiding. They say that some were rescued here and there, but I don't know anyone. And in a way, Kastoria didn't have Jews anymore. Of course it didn't. What happened to their houses, their houses, their shops? Well, after they stuck these papers as signs and as a seal, the Germans had them. Now, their properties, the Germans must have them. Because no one went, no one from Kastoria was heard searching, in a way, a house of Jews, because they were afraid, since they had them. And in fact, in the house where I was staying, with rent, of course, there was a rafter, which is likely to be preserved and still exists today. I had seen it somewhere, but I don't know if it's still being restored. This rafter had two brothers. Of course, when we say a rafter, they made decorations, handkerchiefs, clothes and so on. In that shop over there, I remember it, because it was downstairs, that it had the seal on the door, that it was Jewish. Now, what happened to the Jews' property? I don't know. The Germans would have taken it. If someone had a relationship, because something was heard, without me knowing, that he had a friend or had a relationship with a Jew, he would say that the Jews were well. That is, the Kastoria man was So, I imagine that some were rich very quickly. Yes, not rich, but they benefited. Can you tell us some names? No, no names, I don't know. What I heard in the coffee shop was that the Jews were well. What do you mean, the Jews were well? The Jews had sent them. And who inhabited their houses afterwards? I don't know what happened. The Jews stayed. Of course, they had rights, those who returned. Now some Jews returned. Those were their own houses and shops. I don't know how they benefited from their return. Apart from Mosico, did you see other Jews that you knew return? Those who had the representation of the singers Eliau, they must still exist today in Kastoria, I think, but I don't know what they have to do with Eliau, if they were their children and returned or not, because now they are young children. If they were their grandchildren, I don't know, they returned. Other Jews that returned, I can't remember in Kastoria. But what exists today, I know, it's been many years since I went to Kastoria and I saw that they sold threads in Eliau's shop. Mr. Tasso, until when did you stay in Kastoria? Until 1947, when I finished high school. In 1947, I left and came to Thessaloniki to study. How was Thessaloniki back then? Do you remember? Of course. This street here, where we are now, Vassilis Orgas, were the best houses of the Jews. Not only that, but also the ungodly ones. This house belonged to Nehemia, who, in the end, still had to live. His father was a king. And I remember the house, the old one, because I bought this property on the plans, before the old house was demolished. And all these houses were Jewish, they were the best houses, but also the commercial ones. What was the situation like when you came here? As far as I can remember, and I say this with a bit of respect, the new beach was like this, at the edge of Salamina. I went to see my wife and the children, and we threw stones at them. Like a sea? Yes, like a sea. It was covered with the Jewish cemetery. The Jewish cemetery was St. Demetrios, opposite Evangelistra, on this side, and today it is the University of Macedonia. No, not Macedonia. Aristotle? No, not Aristotle. What other university is there? Macedonian? There is Macedonia and Aristotle. Yes. At this corner was the cemetery. The cemetery was on the side, and from there I remember the trucks, with their eyes looking up, because this must have happened in 1947-1948, as I am telling you now. The trucks were looking up, they were carrying them and throwing them towards the white tower on the beach, and it became a part of the new beach. Were you at the white tower or at the university? I was at the university. But they were going down, and I knew that the trucks were going to the beach. They were carrying plates, bones, I don't know what else to say. I remember the cemetery, I used to pass through it many times, from the house near St. Demetrios, to the university with my feet, and I passed over the cemetery many times. And I remember it well, to live with the bags and the plates, with the memories, all at the beach. When you went to the university for the first time, what did you see in the area, in the old cemetery? How was it? Can you describe it to us? Yes, of course. The old cemetery was completely empty, this university that you call Macedonia, if it's called like that, I don't know, it was a single space, with a bit of an underpass. And here, because there were no Jews, without thinking too much, like me, we passed from up there, and we went to the university. And in fact, next to the cemetery, was the gymnasium of Hercules. What is it called? The stadium. The stadium of Hercules. At that stadium, we did gymnastics as students. That's where we went to do exercises. From up there, this whole space, up to the stadium, was the whole cemetery of the Jews. Which was destroyed, and all these buildings were burned. When you started telling me about this case, when they were plundering the beach, with all the broken plates, you said, you were impressive, and you said, of course, this is not a good memory. If there were Jews, or some Jews, with some strength, they might have saved it, out of respect for the dead. But there weren't people who would say, where are you going? I don't know from which terms this space was destroyed. The municipality must have destroyed it, because they moved the land towards the beach. There were no Jews, I don't know, who resisted this situation. We're talking about 1947-1948. What did you do in 1947 in Thessaloniki? I was a student. I studied for pain. Did you have Jewish classmates? Yes. I had a student, and he was a bit repulsive, but I can't remember his name. Did you study for pain? Yes, we were together, but it didn't end. And we met in a common room, where there was pathology. I don't know exactly if he was a geography student, or a naturalist, or a chemist, or another school, because pathology, and so on, all schools did it, and we were in the same room. I remember him there. Did you have other Jewish students? No. I can't remember. It was rare, how many Jews were left. When did you meet Jews in Thessaloniki again? What? Did you meet Jews in Thessaloniki again? No. In Thessaloniki, I went to the bookstore, and most of the books and French magazines that came out each month, were from the bookstore of Molch. And here, from Deli, from Nakhmia, where I met him, where he had his house. Mr. Tasso, we will stop for a moment to talk to my co-workers, and we will say it again. Cut. Three, two, one, and go. Mr. Tasso, I have some questions to ask you, if you can remember. The Italians, you told us about the Italian occupation, it was much more human, much more human situation. Was the situation so idealistic? Mr. Tasso, do you remember any negative incident? What they have no comparison with the Germans, is well known. What I remember is, only once, a group of executioners, who killed a dozen people, from Kastrovyans. These Kastrovyans, they took them from Kastrovyans, or from the villages, as co-workers of the soldiers. They went outside, to Maniaki, I don't think it was. At the executioner's request, they killed them and left. When they went, the mayor with the carts, to take them, they found one less. He fell unconscious, he didn't get hit, and when, as they say, the executioner, the one with the last gun, he was motionless, and the he had a small bottle, and he was well known, from all the area, how he escaped, how he escaped. He went and entered with the cart. Do you remember his name? Eh... Sako... Excuse me, I want to ask my wife, Canina... What? The car, the one that was at Tasso, what was his name? Tsarukas. Eh? Tsarukas. I think you told us that before. An amazing incident, what you narrate with the Jewish horoscope, that goes to your relative, your sister, your aunt, in Kastoria. Do you remember the names? First of all, Aftounou, what was his name? He was alone, but I don't remember exactly, I don't remember his name, we used to call him by his name, but I don't remember how it was called. This is what my relative says to me, who is now in the school, in Kourissos. What is her name? Anna Antoniou. Anna Antoniou, Anna, she is my relative's wife. His grandfather, his great grandfather, he had a discussion with the Jew, and he suggested to him, as he says to me, now he is my relative, and he suggested to keep him. And the Jew said, no, we will put you in, because the Jew said, if we put you in, you will come back to the village. How did the grandfather say that? Torofias. Torofias, the opposite. Torofias, the opposite. His son was Ioannis, and his daughter is my relative, my great-grandfather's niece. You said Mrs. Antoniou. Mrs. Antoniou, yes. The grandfather was the one who suggested it to me. Were there other cases like this, that fell into your hands, from Kastorians, who tried to help the Jews of Kastorians? I don't know, in detail, I don't know, I don't know. However, there was something in the coffee shop, let's say, that the Jews were good, one who was well-off, they said, the Jews were good for him. I will ask you again about this, because it has to do with the shops, what you described to me, with this Rafti, who had taken the shop of a Jew, were there other cases like this, from Kastorians, who took the shops of the Jews? After the Jews left, of course, all these things were used. Now, who took them, and how did the Kastorians take them, they all work. In any case, the construction situation in Kastoria changed, many houses were built and so on. I don't know, in detail, how they did it. Not for now, but until 1947, when you left, did you see the shops being taken? No, no, no. They were bound, of course, I don't know how. But Rafti, how did he take this shop? Let's be honest, who was Rafti? Rafti was sitting under my house. Who could have taken him? No, I want to say, you had told us, that there was someone, who opened Raftadiko, in a Jewish shop. That is, that he had taken an empty shop, and he opened Raftadiko. Or do I remember wrong? No, you don't remember, not even if I told you, but you don't remember for sure. Maybe you are arguing with Rafti, who was under our house. They were two brothers, they were opposite, and the shop was closed. These were Jews, Rafti? Yes, Jews, and in fact, we had no communication with them, for the same reason, that the road, the one that was horizontal, that we enter the castle, and exit from the north side, all the left and right were shops. No house, and on top of that, houses. But no house, did not communicate from this road. We went up, where today is, the commercial bank, the national bank, are some stairs, and the doors, the entrances of the houses, were from the upper side, not from the main road. In the main road, there were only shops, and on top of the houses, without doors. The doors were from the upper side, we were going back. That is, after they gathered the Jews, this house of Raftado, remained empty. Yes, it remained empty. Of course, no, we were staying there, with a husband, in the upper house. My brothers and I, after we left, we went to Kalithea, up there. The shop, what happened? Now, somewhere, where I had spent years, I say, I do not know, if they have left it, as a reserve, or not, because it looked a little, and I do not know even today, if it exists, if it is a reserve, or not. I would like one more clarification, what I would like. In your whole narrative, I see Germans. Was there no one to help the Germans? On the other hand, was the Greek garrison helping them, in Kastoria? Was someone helping the Germans? Not to help them, the garrison, I do not know if there was a garrison, and so on, but I do not know how to help them, I do not have such an immediate response. As a child, when you went to the cafes, did you not see at all, sometimes, garrisons with the Germans? No, no, garrisons with the Germans, no. Let me tell you something else, what I remember from the Germans, apart from the raids they did outside, in the villages, they were probably not from Kastoria, they came mostly from Dolemaida, or from Aminio. In Kastoria, it was, what I remember vividly, the guard, who was called a gaolaiter, with a piece of iron on his chest, and he came back from a coffee shop, and asked for a snapshot. Snaps, coming to our coffee shop, we filled his glass with ouzo, and he went to another place. And one creation, it was not a reason, young children, they were not more than 19 years old, it seemed to them, that we did not see them before, but in the afternoon, every afternoon, they would return in order, singing, and they would go to the barracks, they were the Germans, that we had in Kastoria. And the Musak children, they were not yet educated, and the gaolaiter. What makes me very impressed, is that all the institutional institutions, in Kastoria, that is, the Greeks, are invisible. That is, there were no police, no mayor, no president, everything was there. Do you remember them? What position did they have, in relation to the Germans? What relationship they had, I do not know. Of course, I remember the mayor, I cannot remember the name of the mayor, but the police and so on, they were there. A mayor came to me, let me tell you, that at some point, the Germans left Kastoria. The Germans were liberated, and they left. I do not know why, maybe they went to some distance, maybe to Aminio. Meanwhile, at the same time, on the same day, some guerrillas came, with their weapons, I saw them, and in the afternoon, they returned to Germany. They had not left officially. And as soon as they saw them, with the weapons of the law and so on, they began to leave, and the Germans began to shoot. And I saw with my own eyes, the Karo, which they brought, I did not see them there, this was happening, before we entered Kastoria, 200-500 meters away from me, I did not see them, I only heard the gunshots. But I saw the Karo, with the bodies, which I carried, and in fact, I did not take them to Kortafia, I had to take them to a village, from which they came, from which they returned. I remember that. And they returned to Germany, and they left in good spirits. I will ask you again, because something does not suit me here. Didn't the guards come to the cafe? Didn't the mayor come? Didn't you hear them talking? Didn't the Germans come? No, the Germans did not come. The Italians came. But the Germans never came. But the guards had to come. I can't remember, but the guards did not come to the cafe. They did not come. If they had come now, and drank a little bit, I can't remember. Outside? Didn't you see any Kastorians talking to Germans? No, except for the doctor, he was a gynecologist. When they left, I did not tell you earlier, but the Germans left and came back. The next day, when they returned, the next day they gathered us in those houses, that I told you were the Jews' and were like a cemetery. And they gathered us all there, and the doctor came out, who studied in Germany and knew German. I remember that thing, that if you have confidence, the Germans did not leave, so don't be afraid. I knew this collaboration with the doctor. And what did the Kastorians say when they heard this? I can't say anything. We were sad because they came back. Were there Jews in the villages, in other cities, in Gozani? In Gozani, a Jew stepped on someone and he left. We were laughing. A Jew could not stand in Gozani. And why? Because the Jews realized that the Gozani people are smarter than the Jews. And no one stayed. How did they realize it? There is, of course, if it is true, or if it is a vision that no one imagines, that with a pepon that they told him how to live, how to use it, is the pepon, you will eat it. Gozani said to the Jew, you will go to the cinema to eat the seeds, and you will give the seeds to the Jew. When the Jew heard these things, he said to him, here we are not caught, and they left and came to Kastrogana, because the Kastroganis were known as bundaladas. Let me tell you this, it is not important. The Kastroganis were interested in the dollar, the gun, the commerce. But in the private life of the family, they were not caught, they had no comparison. Is there any other episode that you remember to tell us, from all this experience of occupation? A short episode, of course, I go to the high school in the morning, all the way, in winter, and as I travel more, I meet a Jew with the star, I remember him on my right, and another one comes down, who was eating, he was eating a piece of land. I remember this rope, I remember it alive, as soon as the Jew approached him, in front of him, he did this, with his finger, and the other one from above, broke a branch, and broke it. When did this happen? This was from the Germans, where there was the star, there was the star. It was in Sparamaunes, I will say that many Jews suffered, because what the Jews were selling, in secret, of course, so that they could eat, there were poor people, Jews who could not stand it. Did you see such Jews selling their things to live? We heard, we did not see, but we heard. I am talking about when it was the Germans, not before the Germans, not with the Italians, but I did not see. But I know what happened. Thank you very much, Mr. Tasso. You are welcome. Cut. Three, two, one, go. Mr. Tasso, you said that the Germans returned. How long did they stay in Kastoria? I mean, they had not left officially. They left in 1944. In 1944, in autumn, I remember that as soon as they left, the guerrillas and the villages were full of guerrillas. They left officially, while the first time they left, it was during the day. I do not know why they left, I do not even know why. But I remember that that day, the episode happened where five or six people were killed. Now, you are talking about the guerrillas who went and liberated Kastoria. Tell us something more, if you have to be told. What did you see? The guerrillas, in all the mountains, were full of guerrillas everywhere. They became, I do not know if I told you about the episode with Glisoura or not, they made a encampment outside our village, and two Germans were killed. In the front, something similar happened in Glisoura, where, contrary to the Germans, 140 women were killed. Fearing our village, because the encampment was outside our village, they went around the mountains, around some places, to hide. Then they gathered the Jews, and the Germans were busy with the Jews. Otherwise, we would have the same incident with the Glisouras, but also one who had some connection with the Germans, Tziforas, he brought a German officer, on a Sunday, at the time when the church was in action, and he told him that these people are religious, they are quiet, they have nothing to do with the encampment that the Germans made. I remember that you told us this in the beginning. I want to say that the rebels entered Kastoria, and in some way, after the Germans left. They stayed for a while, the episodes took place in Athens, the English army came, and of course, I remember, I have an episode with this, and I was a little confused. We entered on the asphalt, in my village, and there were English people, not only English, but also with scarfs, I think they were Jews. And in one of these cars, I ran and jumped to get on top with them. As I was leaving, I did like this with the balami, I was pushing the other one, and they misunderstood me, because next to me there was a child, Christ and all, with the red flag, the communist one. I turned to him and I did this hand gesture, but they took me away from the village, and I made a statement about the organization of the youth of Eyan, and I was afraid that I would go back to the village for a long time, because I didn't return to the village, because the children of my village would take me away. In fact, Munza was directing what held the red flag, the communist one, and not all the other children that were with us. And the English came, the events happened what happened in Athens, and the war was over, the national state took over, and now, we had the civil war, and after the civil war there was the martyrs, it was the worst thing that I remember from my childhood. Is there anything else that you remember about the occupation and the liberation, and you want to tell us? I can't remember anything else about the liberation, the Germans left, the guerrillas entered, there was a period of time that passed, and the national army came, the government took over, and we didn't have... In other areas, the reason I ask you is that we heard from other witnesses that in other areas the guerrillas entered houses and shops and they took things and so on. No, because when they left, they took the Jews, until the guerrillas came, it took two years. They took the Jews in 1943, I can't remember exactly when it was, and the Germans left in 1944, and the guerrillas came one or two years later. What can the guerrillas take from all this? So I understand that nothing was left? I don't know if they left anything, I don't know if they left anything. Who left? Who took them? The municipality, the authorities, not the residents. The residents, if they took something with good intention with the Jews, yes, but not to break houses or shops, the Castorians. Do you know of such Castorians who were guarded, or the Jews gave them things? No, I just heard in the cafe where we were sitting, and the Jews said, let it be, two people were sitting at the table, and they were talking, and someone was saying, let it be, the Jews are good. He was saying, let it be, the Jews are good. That is, he benefited from the Jews and made money, but not to break houses and so on. Do you remember the name of the person they were referring to when they were talking? He was in the cafe, but I can't remember who he was and how he was. Thank you very much, Mr. Tasso. Thank you.